2004
DOI: 10.1002/jssc.200301710
|View full text |Cite
|
Sign up to set email alerts
|

Separation and determination of active components in Radix Salviae miltiorrhizae and its medicinal preparations by nonaqueous capillary electrophoresis

Abstract: A nonaqueous capillary electrophoresis (NACE) method was developed for simultaneous assay of three bioactive components (1: cryptotanshinone; 2: tanshinone IIA, and 3: tanshinone I) in Radix Salviae miltiorrhizae and in its herbal preparations for the first time. After optimization of separation conditions, a buffer of 250 mmol L(-1) ammonium acetate containing 30% acetonitrile and 1.0% acetic acid (V:V) in methanol was selected for separating the three analytes, but baseline separation of tanshinon I and tans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 26 publications
1
44
0
Order By: Relevance
“…Tanshinone IIA (Tan-IIA; C 19 H 18 O 3 ) is extracted from Danshen (Salviae miltiorrhizae radix) (1,2). Tan-IIA exerts antitumor activity in a variety of human cancer cells, such as lung (3), breast (4,5), hepatic (6), pancreatic (7) and colon (8).…”
Section: Introductionmentioning
confidence: 99%
“…Tanshinone IIA (Tan-IIA; C 19 H 18 O 3 ) is extracted from Danshen (Salviae miltiorrhizae radix) (1,2). Tan-IIA exerts antitumor activity in a variety of human cancer cells, such as lung (3), breast (4,5), hepatic (6), pancreatic (7) and colon (8).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional herbs are widely accepted as a valid method of treatment of various forms of human cancer and a considerable effort to develop alternative medicines is currently underway (3). Tanshinone IIA (Tan-IIA; C 19 H 18 O 3 ) is one of the active constituents of Danshen (4,5). Tan-IIA is toxic to numerous human cancer cells, including Colo205 colon cancer (6), MDA-MB-231 breast cancer (7), A-549 non-small cell lung cancer (8), H-146 small cell lung cancer (9) and Hep-J5 hepatocellular carcinoma cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…Danshen (Salviae miltiorrhizae Radix) is widely prescribed in traditional Chinese medicine for cardiovascular diseases (6,7). Tanshinone IIA (Tan-IIA; C 19 H 18 O 3 ) is extracted from Danshen (8,9), and possesses anti-inflammatory (10,11) and antioxidant properties (12,13). Our previous studies have shown that Tan-IIA inhibits growth and induces apoptosis in Colo205 human colon cancer cells (14) and MDA-MB-231 breast cancer cells in vitro (15).…”
Section: Introductionmentioning
confidence: 99%